Themes in Motion: Exploring the Linguistic Landscape of Kumasi with Cultural Spectacles (International Journal of Language, Literacy and Translation, 2025)
Inscriptions on vehicles are common in Ghana. However, the themes dominating these inscriptions have received less attention in Ghana’s linguistics literature. The present study explores the linguistic landscape of Ghana to elucidate how the Akan culture is reflected in the various themes that dominate in Akan monolingual signages on commercial vehicles. Photographic images of the texts were taken at different research locations within the Kumasi Metropolis. A total of 114 photos were taken, categorized, and qualitatively analysed. Drawing on Ethnolinguistic Vitality Theory, the study demonstrates that there are a lot of Akan-only texts on commercial vehicles in the city, and the factors such as status, demography, and institutional support account for their presence. The inscriptions convey messages and themes that reflect the Akan people’s culture. The themes highlighted include those connoting; religious belief, good morals/advice, innuendo, poverty, love, regret, and death. Inscriptions on religious belief constitute the highest with 19 percent. The study has implications for language maintenance.